TEACHER PROFESSIONAL DEVELOPMENT: A STUDY OF MOTIVATING FACTORS BETWEEN NOVICE AND EXPERIENCED TEACHERS - Dini Utami Mulyaningsih; Riyadh Ahsanul Arifin (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2021)
Motivation is one of crucial factors to teachers during their professional development. It is well established that motivation can positively increase their growth professionally. This study aimed to find out motivating factors between novice and experienced teacher. In this context, novice teacher is a teacher who has less than 5 years teaching experience while experienced teacher is a teacher who has more than 5 years’ experience. This research employed descriptive study, involving 4 teachers. A questionnaire and a semi structured interview were employed to gain the data. The data were analyzed descriptively. From the study, it is found that there are some similarities between novice and experienced teachers’ motivation. Moreover, it also found that taking postgraduate study gives a positive impact on their teaching practice. Indeed, it is recommended to give teachers more propelling on the importance of teacher need for their professional development.